Dates of hoards in Sweden and the coinage of Stephen I, King of Hungary - Gedai, István (Hikuin, 1985)
In the research of the earliest phase of Hungarian coinage the analysis of the Scandinavian - primarily Swedish - hoards has a special importance, as this area had a decisive role in the foreign trade interests of the Hungarians about the turn of the millennium. We have no data on the beginning of Hungarian-Viking trade; we can, however, assume that it already existed as a peripheral area of the Arabian-Viking trade as early as the period previous to the territorial settlement of the Hungarians. It is a fact that in the 10th century Arabian dirhems occur in Hungary. At that time, however, they were not part of a money circulation but were used as jewels